MENUMBUHKEMBANGKAN KARAKTER RELIGIUS PADA ANAK USIA DINI DI TK KUSUMA KELURAHAN PATOKAN KECAMATAN KRAKSAAN PROBOLINGGO JAWA TIMUR - THOWILAH, TOYYIBATUT (STAI Nurul Huda Kapongan Situbondo, 2021)
Learning can be said to be successful if there is a Behavior Change stage. Learning in early childhood is the initial basis for character building in children. Learning religious values ​​in children from an early age may be important, because education really requires a process such as an interconnected food chain that makes children religious. The research contained in this journal is qualitative research which is descriptive in nature. To collect data, the researcher used two methods, namely: the interview method and the observation method. The results show that learning that fosters religious character in KUSUMA Kindergarten, Patokan Village, Kraksaan District, Probolinggo Regency, East Java, is by combining classroom lessons, routine habituation, spontaneous, and exemplary. A beautiful character education method needs support from all parties who must be actively involved, from the family, community, general or formal education institutions, to national figures and of course religious and community leaders.